Climate Change increases the risk of metal toxicity in Arctic zooplankton - Halsband, Claudia; Thomsen, Nele; Reinardy, Helena C. (Frontiers in Marine Science, 2024)
This mini-review outlines major climate-change exacerbated sources of metal to the Arctic marine environment, leading to measured concentrations sometimes exceeding levels considered environmentally safe, and thus potentially impacting arctic marine zooplankton. We review the bioavailability of metals in Arctic marine environments and the current state of knowledge on metal toxicity in marine copepods. Toxicity response mechanisms to metals included oxidative stress as well as genetic processes of DNA damage and repair. We highlight species-specific differences in metal impacts within the diverse group of planktonic copepods. We summarize observed responses at multiple levels of biological organization, and note that studies on arctic species are scarce and need expansion, as results from temperate and tropical species may not be readily transferable to arctic counterparts. We further provide an updated view on impacts of metals in combination with other stressors in the Arctic marine system in light of increasing attention to multiple stressors of climate change and pollution. For arctic marine zooplankton, a number of research gaps are identified, including a need for integrating effects responses across levels of biological organization, for studies into mechanisms of heritable changes and long-term transgenerational impacts, and considering interspecific capacity for response and adaptation.